Regional and sectoral estimates of the social cost of carbon: An application of FUND - David Anthoff; Steven Rose; Richard S. J. Tol; Stephanie Waldhoff (The Economic and Social Research Institute (ESRI), 2011)
The social cost of carbon is an estimate of the benefit of reducing CO2 emissions by one ton today. As such it is a key input into cost-benefit analysis of climate policy and regulation. We provide a set of new estimates of the social cost of carbon from the integrated assessment model FUND 3.5 and present a regional and sectoral decomposition of our new estimate. China, Western Europe and the United States have the highest share of harmful impacts, with the precise order depending on the discount rate. The most important sectors in terms of impacts are agriculture and increased energy use for cooling. We present an extensive sensitivity analysis with respect to the discount rate, equity weights, different socio economic scenarios and values for the climate sensitivity parameter.
Keywords: 330; climate change; social cost of carbon